Ubiquitous Wasaṭiyyah Dalam Al-Qur'an Perspektif Quraish Shihab - Nawawi Marhaban; M. Anzaikhan; Mustapa (Kuras Institute, 2024)
This study explores the ubiquitous presence of wasathiyah (moderation) in the Qur'an, focusing on Surah Al-Baqarah verse 143 as its foundation. The research aims to understand the Qurais Shihab's interpretation of verses related to wasathiyah across various issues and discourses. This article's position in existing research novelty lies in proving the ubiquitous presence of wasathiyah in the Qur'an, which has not been comprehensively studied in scholarly journals. Despite Qurais Shihab extensively discussing the spread of wasathiyah verses in various situations and conditions in both his Al-Misbah exegesis and YouTube content, this article falls under literature review research with a qualitative approach. The methodology involves descriptive analysis and content study of Qurais Shihab's thoughts, particularly in the Al-Misbah exegesis. The findings conclude that the ubiquitous presence of wasathiyah exists within the contexts of religion, social-humanitarian issues, family, work, economics, and political governance.